Pengembagan Program Kesehatan Mental Remaja Berbasis Komunitas pada Remaja di Desa Bangun Rejo, Kecamatan Tanjung Morawa, Kabupaten Deli Serdang Tahun 2025 - Nopalina Suyanti Damanik; Parningotan Simanjuntak; Sri Deviani; Siti Nurcahaya Angian; Retno Wahyuni (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Adolescent mental health is an increasingly important global issue, along with the increasing prevalence of psychological disorders in early productive age. Adolescents are in a complex transition from childhood to adulthood, which is often accompanied by emotional changes and social pressures (WHO, 2023; Sari et al., 2022). In Bangun Rejo Village, Tanjung Morawa District, there are many adolescents who experience academic stress, family problems, and minimal access to information about mental health, based on initial observations and interviews with community leaders (Simanjuntak, 2024). The purpose of this community service program (PKM) is to improve the Implementation of Community-Based Adolescent Mental Health Program Development for adolescents in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra Province in 2025. The methods used include In this activity, systematic steps are carried out in the form of 1) identification of Toddlers about the Community-Based Adolescent Mental Health Program for adolescents); 2) preparation of materials and steps for the Development of Community-Based Adolescent Mental Health Program for adolescents); 3) implementation of education for the Development of Community-Based Adolescent Mental Health Program for adolescents). Results Based on the results of the implementation of community service for Adolescent in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra Province, there were 50 teenagers involved in the training and education sessions. 10 cadres of teenagers who care about mental health were formed. 1 educational module was compiled on adolescent mental health. The formation of a WhatsApp group for teenagers to share stories and support each other. Increased participant understanding scores from 40% to 85% based on pre-test and post-test (Service Team, 2025). Suggestions It is hoped that long-term evaluations need to be carried out to measure the impact on reducing cases of mental disorders